Tracing the differences in the representation of ‘Queer’ identity found in few 20th and 21st Century novels - Onty, Jannatul Ferdose (Brac University, 2022)
This thesis report is submitted in partial fulfilment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2021.